A framework for evaluating cyber forensic tools. (13th September 2022) - Gupta, Sunil; Arya, Pradeep Kumar; Sai, Sri Vemuri Dwijesh; Nagandla, Sri Sai Bhargav
Digital forensics has always been a versatile and high stress field. Perpetrators use various methods to commit crimes and find ways to evade the authorities. Forensic investigators use automated software tools to gather evidence to present in a court of law. Admissibility of evidence has always been questioned in the court. There have been many methods developed to validate and verify the forensics. But very often, forensic investigators lack resources to conduct some of these tests and as for some of them, they are outdated and do not apply to the current scenario. This study explores such methodologies and introduces a new paradigm which will complement the problems with previously proposed works. The proposed paradigm is not only a fast solution relatively, but it can also be easily used by beginners. We aimed to make the most time effective and cost-effective solution. We have also included a performance testing methodology to make our paradigm more tolerable and fail proof. The proposed algorithm will also specify the total number of observations that need to be taken to tolerate the errors.